Implementasi Algoritma SAW (Simple Additive Weighting) Pada Aplikasi Penilaian Kinerja Karyawan Cleaning Service PT.Haleyora Powerindo - Kirana, Chandra; Yurindra, Y; Supardi, S (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
In order to improve services to the use of operating services in this case the work of Building Maintenance and Installation or widely known as the Cleaning Service work. PT. Haleyora Powerindo always asks service users to be able to provide performance appraisals that have been determined by the institution for every employee in the service user company. However, the company is currently experiencing problems related to the performance appraisal, because the appraisal is still using the manual method where the branch head has difficulty giving an assessment of employees as evaluation material. In this study the authors will make applications that are expected to provide solutions to these problems. The application design needed by the company, especially for each Branch Unit as an evaluation material, is currently an application that can help support decision making. One method that can be used in this performance appraisal system is the SAW (Simple Additive Weighting) method. The results of the SAW calculations are suitable in making a decision to solve the problem of calculating the results of employee performance appraisals. This performance appraisal application can generate performance reports as decision makers automatically.